2020
DOI: 10.1038/s41598-020-63730-0
|View full text |Cite
|
Sign up to set email alerts
|

Influence of different knee and ankle ranges of motion on the elasticity of triceps surae muscles, Achilles tendon, and plantar fascia

Abstract: Stiffness is a valuable indicator of the functional capabilities of muscle-tendon-fascia. Twenty healthy subjects participated in this study in which the passive elastic properties of the medial gastrocnemius (MG), lateral gastrocnemius (LG), soleus muscles (SOL), Achilles tendon (AT, at 0 cm, 3 cm and 6 cm proximal to the calcaneus tubercle, corresponding to AT0cm, AT3cm and AT6cm, respectively) and plantar fascia (PF) were quantified when their knee was fully extended or flexed to 90° using shear wave elasto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 49 publications
(80 reference statements)
1
30
1
Order By: Relevance
“…The subject was seated in a reclining chair and maintained 20 degrees of flexion at the ankle joint, 70 degrees of flexion at the knee joint, and 80 degrees of flexion at the hip joint as measured by a goniometer. In this limb position, the ankle is more flexed than the slack angle, which relaxes the triceps surae muscle [6][7][8]. In this limb position, the ankle joint was flexed for the tibialis anterior muscle to keep slightly elongated.…”
Section: Experimental Protocolmentioning
confidence: 99%
See 2 more Smart Citations
“…The subject was seated in a reclining chair and maintained 20 degrees of flexion at the ankle joint, 70 degrees of flexion at the knee joint, and 80 degrees of flexion at the hip joint as measured by a goniometer. In this limb position, the ankle is more flexed than the slack angle, which relaxes the triceps surae muscle [6][7][8]. In this limb position, the ankle joint was flexed for the tibialis anterior muscle to keep slightly elongated.…”
Section: Experimental Protocolmentioning
confidence: 99%
“…An attempt to estimate the resting muscle tension during passive motion of the ankle and knee joints was made mainly in the medial and lateral gastrocnemius and soleus muscles, where the slack angle was determined. The elastic modulus was increased by the muscle elongation, in which the muscle was stretched from the slack length [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be related to the different activity patterns and exercise intensity between the PF group and healthy group. According to previous studies, the more activity or exercise intensity, the greater the stiffness of AT (Engkananuwat et al, 2018;Schneider et al, 2018;Zhou et al, 2019a,b;Liu et al, 2020;Siriphorn and Eksakulkla, 2020).…”
Section: Optimal Cut-off Point In Assessing Chronic Pf Patients With Swementioning
confidence: 91%
“…Reduction of the AT force may decrease the plantar fascia load (Chen et al, 2015). Moreover, previous studies have demonstrated that stretching can decrease tendon stiffness (Zhou et al, 2019a,b;Liu et al, 2020). Therefore, lengthening or tension relief of the AT, especially in participants with tight AT, may be beneficial in terms of plantar fascia stress relief (Cheng et al, 2008).…”
Section: Stiffness Of the At Between Individuals With And Without Pfmentioning
confidence: 99%